Changing Paradigms in Acute Care Surgery: A Shift to the Hindgut. Issue 1 (January 2014) - Mishra, Nitin; Roberts, Patricia L.; Marcello, Peter W.; Read, Thomas E.; Hall, Jason F.; Schoetz, David J.; Ricciardi, Rocco
In this study we sought to identify changes in the etiology and surgical treatment of acute gastrointestinal perforations in the United States over the past 20 years. We performed a retrospective review of the Nationwide Inpatient Sample from January 1, 1988, through December 31, 2007. We first identified all patients with gastrointestinal perforations, the perforated organ, and treatment rendered. During the study period, 550, 132 patients experienced a gastrointestinal perforation for a mean rate of 3.9 cases per 1, 000 discharges. Total number of perforations rose significantly over the study period, yet surgical procedures were performed in less than half of the patients (47.6%). The most common surgical procedures for gastrointestinal perforation were colorectal in origin (38.3%), upper gastrointestinal tract (30.0%), small intestine (29.2%), esophagus (3.0%), and anus (0.1%). At study end, colorectal procedures for perforation were the most commonly performed (40.4%), whereas upper gastrointestinal procedures experienced the greatest decline. In conclusion, our data demonstrate a decline in procedures for upper gastrointestinal perforation and an increase in colorectal procedures during the two-decade study period. These data should be used to assist in the training of acute care surgeons.